Price Perception and Online Promotion Effects on Brand Awareness and Purchase Decisions for Kaiamuslimwear Kurta - Desi Sulastri; Hari Muharam; Agus Setyo Pranowo (PT. Maju Malaqbi Makkarana, 2026)
This study examines the influence of price perception and online promotion on brand awareness and its implication for purchase decision for KaiaMuslimWear kurta products. The issue addressed in this study is the need for KaiaMuslimWear to strengthen its competitive position in the Muslim fashion market, particularly in the men’s kurta category, where consumers are exposed to various product alternatives, competitive prices, and intensive digital promotion. This study used a quantitative approach with a descriptive and verificative design. Data were collected through an online questionnaire distributed to 200 KaiaMuslimWear consumers and analyzed using SPSS 27 and LISREL 8.80 with Structural Equation Modeling. The results show that price perception and online promotion have positive and significant effects on brand awareness and purchase decision. Brand awareness also has a positive and significant effect on purchase decision. Furthermore, brand awareness significantly mediates the effect of price perception and online promotion on purchase decision. These findings indicate that purchase decision is shaped through an integrated process involving perceived price fairness, online promotional effectiveness, and consumer awareness of the brand.